Modelagem de fluxo de informações administrativo-financeiro no projeto de máquinas agrícolas - Silva, Junior Rogerio da (2014)
Nowadays, the agricultural industry is undergoing several transformations, both economically, due to production costs. Among the main highlights is the inclusion of multinational companies, attracted by the performance of the Brazilian market and changes in the conception of agricultural machinery, with differentiated and more attractive design. The government incentives offered to producers using soil cultivation as a livelihood, have increased significantly, causing companies mobilize to market an economically viable agricultural machinery, however, a return on invested capital is necessary for these organizations, through a calculation of the economic and financial viability adequate. This work shows a model of information flow in the area of administrative-financial knowledge applied to project of agricultural machinery, identifying the activities to be performed in project management, integrating to other areas involved in the creation of a new product focusing on the return of investment. The model includes created from the formation of the project team, financial participation of experts, until the approval of the general document that demonstrates the feasibility of the project through all relevant checks to the general control of product design details. The model serves as a basis for further study of undergraduate and graduate degrees in economic viability analysis, searching for information in the field of administrative-financial knowledge, applied to project management in the design of agricultural machinery, and also for companies working on similar products, as an essential tool to aid in determining the time of return of the amount invested in product design.